Pola Bakteri Aerob pada Sampel Sputum dan Uji Sensitivitas Antibiotik Pasien Rawat Inap di Rumah Sakit Islam Sitti Maryam Manado - Aiko Budiman; Heriyannis Homenta; Fredine E. S. Rares (Syntax Corporation Indonesia, 2025)
Sputum is material expelled through the mouth from the respiratory tract via the coughing mechanism. Coughing can easily transmit pathogenic microorganisms. Microorganisms produced by coughing can infect anyone. Antibiotics are drugs used to treat infectious diseases caused by bacteria. The misuse of antibiotics leads to an increase in antibiotic resistance. This study aims to identify aerobic bacteria in sputum samples and to determine the antibiotic sensitivity of bacteria in sputum samples from inpatients at Sitti Maryam Islamic Hospital, Manado. The type of research is descriptive with a cross-sectional design, which involves bacterial identification using Gram staining, biochemical tests, and antibiotic sensitivity tests. The results showed 12 samples, consisting of 8 Gram-positive bacteria and 3 Gram-negative bacteria, with 5 types of bacteria identified: Staphylococcus sp., Staphylococcus aureus, Bacillus sp., Streptococcus sp., and Sphingomonas paucimobilis. The sensitivity test results indicated that Gram-positive bacteria were sensitive to meropenem, amikacin, and ciprofloxacin (100%) but resistant to ampicillin. Gram-negative bacteria were sensitive to gentamycin, amikacin, ciprofloxacin, sulfamethoxazole/trimethoprim, aztreonam, and meropenem but resistant to aztreonam. The most commonly found bacteria were Staphylococcus sp., Sphingomonas paucimobilis, and Bacillus sp., which were sensitive to meropenem, amikacin, and ciprofloxacin, but resistant to ampicillin and aztreonam.